Web-based Learning Technologies in Translation Studies: Undergraduate Students’ Views - Burkšaitienė, Nijolė (Journal of Education Culture and Society, 2025)
Aim. The impacts of web-based learning technologies have been widely investigated across different countries in many fields of university studies. In Lithuania, however, little known research has investigated their use in translator training. Thus, the present study attempts to address this gap by analysing undergraduate translation students’ experience of and their views regarding the use of web-based learning technologies in their studies. Methods. In the present small-scale qualitative research, the data was drawn from 34 essays written by undergraduate majors in translation and analysed using the inductive content analysis. Results. The study revealed some categories and subcategories of educational benefits and challenges caused by the use of these technologies as seen by the students themselves. Conclusion. The results demonstrate that most students considered that using web-based learning technologies was both a positive and negative experience, several students viewed this experience as being solely positive and one student’s experience was negative. To overcome negative effects, it is recommended to raise students’ awareness of the potentially harmful effects caused by their excessive use as well as to develop the skill of managing the amount of time spent using them. Cognitive value. The present study is one of the first focused on the use of such technologies by future translators in Lithuania to date. Even though its sample size is small, its findings deepen our understanding of translation students’ views regarding the use of such technologies in their studies. In this way, the study contributes to the theoretical considerations and empirical procedures in the field and calls for further research.